Shocks, Physical Characteristics, and Risk Taking Behaviour - SANJAYA, Muhammad Ryan (Asian Journal of Empirical Research, 2013)
Many conventional economic analysis assumes that risk preference is taken as given and do not give much scrutiny on it. However, empirical studies show that risk preference is not random: shocks and predetermined characteristics can determine risk preference. This study tried to see if these potential determinants are together affect risk aversion in Indonesia using 2007 micro data. The author found that there is limited evidence that shocks and predetermined characteristics can affect risk preference. There is a preliminary indication that risk preference was not only driven by the individual’s wealth and demographic factors (that can be easily controlled), but also by the individual’s time preference.